2006
DOI: 10.1111/j.1442-2050.2006.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of esophageal acid exposure at 1 cm and 6 cm above the squamocolumnar junction using the Bravo™ pH monitoring system

Abstract: The aim of this study was to assess the quantitative differences of acid exposure at 1 cm and 6 cm above the squamocolumnar junction (SCJ) using two radiotelemetry pH capsules affixed to the esophageal mucosa. Ten normal subjects and 10 endoscopy-negative gastroesophageal reflux disease (GERD) patients without hiatus hernia (ages 20-54, 12 male) were studied for a 24-h period using the Bravo pH monitoring system. pH capsules were placed 1 cm and 6 cm above the SCJ. Interpretable data for at least 14 h was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
2
15
0
7
Order By: Relevance
“…This degree of variation in positioning the probe may lead to inconsistencies in pH measurements, given the gradient of acid exposure in the distal esophagus that has been documented in both patients with GERD 12 and in normal subjects. 13 This inconsistency in pH probe placement can affect clinical management by reporting false positive and false negative pH monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This degree of variation in positioning the probe may lead to inconsistencies in pH measurements, given the gradient of acid exposure in the distal esophagus that has been documented in both patients with GERD 12 and in normal subjects. 13 This inconsistency in pH probe placement can affect clinical management by reporting false positive and false negative pH monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that the Bravo system is capable of distinguish between GERD patients and controls with sensitivity of 84% and specificity of 85% (18) . Acid exposure is greater just above the squamocolumnar junction (22) , however, by convention, in catheter-based pHmetry the tip of the probe is positioned 5 cm above the LES to prevent migration of the pH sensor into stomach, due to esophageal shortening during swallows, which in turn could lead to record false episodes of acid reflux (8) . Bravo system monitors pH with a capsule attached to esophageal mucosa, therefore, in a fixed position in relation to LES, overcoming this limitation seen with catheter-based pHmetry (21) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that wireless pH monitoring performed at 1 cm instead of 6 cm above the SCJ could enhance sensitivity and specificity of wireless capsule pH monitoring compared to traditional pH monitoring [19]. However, a recent study by Bansal et al [20] has shown that wireless pH monitoring performed at 1 cm above the SCJ does not improve the sensitivity or specificity of wireless pH monitoring compared to monitoring performed at 6 cm above the SCJ.…”
Section: Bravo Ph Monitoring Is Accurate To Detect Gerdmentioning
confidence: 94%